Pengaruh Kepemimpinan, Motivasi Kerja Dan Kepuasan Kerja Terhadap Kinerja Karyawan Pada Perusahaan Daerah Air Minum Surya Sembada Kota Surabaya - Shafira Bani Anshori; Aniek Maschudah Ilfitriah (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study aims to examine the effect of leadership, work motivation, job satisfaction on employee performance. Based on the objectives of this study, the research design is very suitable using a quantitative approach with a descriptive approach. The variables chosen to be examined in this study are Leadership, Work Motivation and Job Satisfaction on Employee Performance. The population in this study were employees of the Regional Drinking Water Company of Sembada Surabaya in the section on water usage, accounts and payments, and the human resource development system with a total of 85 employees. By using the Slovin formula, the number of samples that will be used as respondents in this study is 70 respondents. The sampling technique used is purposive sampling. The results of this study show that leadership has a positive and significant effect on employee performance, and work motivation has a positive and significant effect on employee performance, as well as job satisfaction which has a positive and significant effect on employee performance at the Surya Sembada Water Supply Company, Surabaya. Keywords: Leadership, Motivation, Satisfaction and Performance